Association between mental illness and COVID-19 susceptibility and clinical outcomes in South Korea: a nationwide cohort study - Lee, Seung Won; Yang, Jee Myung; Moon, Sung Yong; Yoo, In Kyung; Ha, Eun Kyo; Kim, So Young; Park, Un Min; Choi, Sejin; Lee, Sang-Hyuk; Ahn, Yong Min; Kim, Jae-Min; Koh, Hyun Yong; et al. (The Lancet. Psychiatry, 2020)
Evidence for the associations between mental illness and the likelihood of a positive severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) test result and the clinical outcomes of COVID-19 is scarce. We aimed to investigate these associations with data from a national register in South Korea. A nationwide cohort study with propensity score matching was done in South Korea using data collected from the Health Insurance Review and Assessment Service of Korea. We defined mental illness as present if one of the relevant ICD-10 codes was recorded at least twice within 1 year for an outpatient or inpatient. Severe mental illness was considered as non-affective or affective disorders with psychotic features. We included all patients aged older than 20 years who were tested for SARS-CoV-2 through services facilitated by the Korea Centers for Disease Control and Prevention, the Health Insurance Review and Assessment Service of Korea, and the Ministry of Health and Welfare, South Korea. We investigated the primary outcome (SARS-CoV-2 test positivity) in the entire cohort and the secondary outcomes (severe clinical outcomes of COVID-19: death, admission to the intensive care unit, or invasive ventilation) among those who tested positive. Between Jan 1 and May 15, 2020, 216 418 people were tested for SARS-CoV-2, of whom 7160 (3·3%) tested positive. In the entire cohort with propensity score matching, 1391 (3·0%) of 47 058 patients without a mental illness tested positive for SARS-CoV-2, compared with 1383 (2·9%) of 48 058 with a mental illness (adjusted odds ratio [OR] 1·00, 95% CI 0·93-1·08). Among the patients who tested positive for SARS-CoV-2, after propensity score matching, 109 (8·3%) of 1320 patients without a mental illness had severe clinical outcomes of COVID-19 compared with 128 (9·7%) of 1320 with a mental illness (adjusted OR 1·27, 95% CI 1·01-1·66). Diagnosis of a mental illness was not associated with increased likelihood of testing positive for SARS-CoV-2. Patients with a severe mental illness had a slightly higher risk for severe clinical outcomes of COVID-19 than patients without a history of mental illness. Clinicians treating patients with COVID-19 should be aware of the risk associated with pre-existing mental illness. National Research Foundation of Korea.